FAKTOR DETERMINAN KEPUTUSAN PEMBELIAN GENERASI Z DI SHOPEE DETERMINANT FACTORS FOR PURCHASE Z GENERATION IN SHOPEE - Bakri, Adzan Noor; Hardianti, Dini (IAIN Batusangkar, 2020)
The purpose of this research was to describe the determinant factors influencing purchasing decision of Z generation in Shopee. The design of the research was quantitative research by conducting a survey to students of Faculty of Economics and Islamic Business, IAIN Palopo. The results showed there were several factors that influenced purchasing decision of Z generation in Shopee, namely (1) social class, (2) personality, (3) economic environment, (4) motivation, and (5) learning process.